Language Style Variation and Sociocultural Function in the Karang Pendem Community: A Sociolinguistic Analysis - Wulantari, I Gusti Ayu Dhiva; Syahid, Agus; Miswaty, Titik Ceriyani; Sudewi, Ni Ketut Putri Nila; Muhlisin (Lexeme : Journal of Linguistics and Applied Linguistics, 2026)
This study investigates language style variation in everyday social interactions among residents of Karang Pendem, Cakranegara. Using a qualitative descriptive method, the research observes and analyzes spontaneous language use in natural settings such as homes, markets, temples, and public gatherings. Data were collected through field observations and detailed note-taking, and analyzed using theories of sociolinguistics, particularly Labov’s theory of variation, Holmes’ sociopragmatic approach, and Hymes’ communicative competence. The findings reveal four dominant categories of style-shifting based on interlocutor: (1) to elders, marked by respectful forms and high Balinese (basa alus); (2) to peers, characterized by informal tone, casual Indonesian, and code-mixing; (3) to strangers or outsiders, involving formal Indonesian and neutral speech; and (4) to children or socially subordinate individuals, featuring directive, simplified language. These shifts are shown to be strategic and culturally encoded, reflecting values such as respect, solidarity, and caution. The study concludes that style-shifting is not merely a linguistic habit but a culturally informed social strategy. Language variation in Karang Pendem operates as a tool for managing relationships, reinforcing social roles, and maintaining community norms. The findings affirm that language style functions both as a medium of expression and as a reflection of deep-rooted sociocultural structures.